The Role of Strategic Absorptive Capacity in Linking Employee Engagement, Corporate Culture, and Customer Relationship Management to Improve Business Performance: A Study of Ayam Geprek Culinary MSMEs in Bekasi City - Bunga Ramadhani; Anisa Rahmawati; Selvia Selvia; Nurina Putri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study investigates the strategic role of absorptive capacity in mediating the effects of employee engagement and corporate culture on customer relationship management (CRM) and business performance in culinary micro, small, and medium enterprises (MSMEs) in Bekasi, Indonesia. Grounded in the Dynamic Capability Theory, this research explores how internal organizational factors enhance strategic capabilities to address competitive challenges. Using a quantitative approach with Structural Equation Modeling (SEM) and data collected from 548 respondents across MSME actors in the “ayam geprek” culinary sector, the study confirms that employee engagement and corporate culture significantly influence absorptive capacity. However, the impact of absorptive capacity and culture on CRM is statistically weak. Notably, CRM directly improves business performance, although it does not significantly mediate the link between absorptive capacity and performance. These findings highlight the critical importance of internal engagement and capability development for sustainable performance, while also suggesting the need for integrating other mediator such as innovation or digitalization to fully leverage strategic capacities. This research provides valuable implications for MSME management and policymaking, especially in enhancing human capital and organizational adaptability within dynamic local markets.